Aktivitas Antijamur Ekstrak Teripang Darah (Holothuria atra Jeager.) Terhadap Pertumbuhan Jamur Malassezia furfur Penyebab Panu - Achmad Mulyadi, Tuti Alawiyah, Siti Khotimah, (Universitas Tanjungpura, 2016)
Holothuria atra is marine creature which is potential as a source of antifungal material.This research aims to find out the antifungal activities of the extract of H. atra against the Malassezia furfur fungus that causes tinea versicolor. The extract of H. atra was obtained through a maceration method using methanol. The antifungal activities were tested using Kirby-Bauer disc paper diffusion method on the Saboraud Dextrose Agar (SDA) medium enriched with olive oil. The research used the extract with concentrations of 20%, 40%, 60%, 80%, and 100% with 2% of ketoconazole positive control and DMSO (Dimethyl Sulfoxid) negative control. The secondary metabolite test indicated content of alkaloids, triterpenoids, and saponins in the extract. The test results of antifungal activities showed that alllevels of concentration could inhibit the growth of M. furfur fungus characterized by the formation of a clear zone around the paper disc. The extract of H. atra is fungistatic with a very strong inhibition category. The concentration of 20% is the most effective in inhibiting the M. furfur fungus with a clear zone diameter of 22,16mm.